(untitled) (City: History, Culture, Society, 2018)
The presented article revolves around an important academic issue pertaining to the spatial and chronological relations in the gords and towns of the 13th century, operating in Poland in the then Piast duchies. In the face of scarce written sources little is known about many 13th century cities, the space they occupied and the development within the city walls. To date, the issues have also been neglected by archaeologists, narrowed down to works accompanying renovations or construction investments. Archaeological research, carried out selectively and randomly, does not contribute to a better understanding of the specific 13thcentury cities. Some of the smaller cities are very poorly researched which also precludes any conclusions on urban space. Therefore, the issue of chronological and spatial relations between gords and cities has not been thoroughly surveyed and it may remain so for a long time. As part of the considerations, selected examples of gords and towns have been presented from the specific historical countries (Geater Poland, Kuyavia, the Gdansk Pomerania,Masovia, Central Poland, Lesser Poland and Silesia) to illustrate the issues in question. At the same time, attempts have been made to refer these examples to models or spatial relations including towns and older settlement as presented by Marian Rębkowski. These considerations lead to a conclusion that the gords and towns in the 13th century often operated next to each other, fulfilling different functions, at the same time complementing each other. In the future, this issue necessitates further detailed research into specific areas like fragmented principalities or the settlement-related activities on the part of the specific princes.